A phase II study of laquinimod in Crohn's disease. Issue 8 (3rd October 2014) - D'Haens, Geert; Sandborn, William J; Colombel, Jean Frederic; Rutgeerts, Paul; Brown, Kurt; Barkay, Hadas; Sakov, Anat; Haviv, Asi; Feagan, Brian G
Abstract : Objective: Laquinimod is an oral therapeutic agent under investigation for the treatment of Crohn's disease (CD), Huntington's disease, lupus nephritis and multiple sclerosis. This dose escalation study evaluated the safety and efficacy of laquinimod as induction therapy in patients with active moderate–severe CD. Design: Multicentre, double-blind, sequential-cohort, randomised controlled trial with laquinimod doses of 0.5, 1, 1.5 or 2 mg/day or placebo (n=45 per cohort randomised in a 2:1 ratio) for 8 weeks with 4-week follow-up. Stable concomittant therapies and prior use of anti-tumour necrosis factor agents were permitted. Comprehensive safety assessments were performed and efficacy analyses included the proportions of patients in clinical remission (CD Activity Index (CDAI) <150 and no treatment failure (TF)), and with a clinical response (70 or 100 point CDAI reduction from baseline or remission and no TF). Results: 117 patients received laquinimod and 63 patients received placebo. The overall incidence of adverse events (AEs) in the laquinimod group was similar to the pooled placebo group (86.2%–96.7% vs 82.5%) and most AEs were mild to moderate in severity. Treatment with laquinimod 0.5 mg showed consistent effects on remission (48.3% (CI 31% to 66%) vs 15.9% (CI 9% to 27%)), response 100 (55.2% (CI 37% to 71%) vs 31.7% (CI 22% to 44%)) and response 70 (62.1% (CI 44% to 77%) vs 34.9% (CI 24% to 47%)) versus placebo. Laquinimod 1.0 mg showed less benefit (26.7% remission (CI 14% to 44%) and 53.3% response 70 (CI 36% to 70%)), and no effect was noted on remission/response at higher doses. Conclusions: Laquinimod was safe and well tolerated, and the effects on remission and response of the 0.5 mg dose suggest a treatment benefit in patients with CD. Trial registration number: NCT00737932.